Novel Genetic, Clinical, and Pathomechanistic Insights into TFG‐Associated Hereditary Spastic Paraplegia. Issue 11 (30th August 2016) - Harlalka, Gaurav V.; McEntagart, Meriel E.; Gupta, Neerja; Skrzypiec, Anna E.; Mucha, Mariusz W.; Chioza, Barry A.; Simpson, Michael A.; Sreekantan‐Nair, Ajith; Pereira, Anthony; Günther, Sven; Jahic, Amir; Modarres, Hamid; et al.
Abstract : Two distinct missense variants at a mutational hotspot in the coiled coil domain of TFG are associated with recessive hereditary spastic paraplegia (HSP). Clinical presentation correlates with the degree of mitochondrial fragmentation as observed upon overexpression of mutant proteins in cultured primary neurons. ABSTRACT: Hereditary spastic paraplegias (HSPs) are genetically and clinically heterogeneous axonopathies primarily affecting upper motor neurons and, in complex forms, additional neurons. Here, we report two families with distinct recessive mutations in TFG, previously suggested to cause HSP based on findings in a single small family with complex HSP. The first carried a homozygous c.317G>A (p.R106H) variant and presented with pure HSP. The second carried the same homozygous c.316C>T (p.R106C) variant previously reported and displayed a similarly complex phenotype including optic atrophy. Haplotyping and bisulfate sequencing revealed evidence for a c.316C>T founder allele, as well as for a c.316_317 mutation hotspot. Expression of mutant TFG proteins in cultured neurons revealed mitochondrial fragmentation, the extent of which correlated with clinical severity. Our findings confirm the causal nature of bi‐allelic TFG mutations for HSP, broaden the clinical and mutational spectra, and suggest mitochondrial impairment to represent a pathomechanistic link to other neurodegenerative conditions.